Training Technical Disciplines Using Information and Learning Environment for the Credit-Module System (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Modular learning is the organization of the educational process in which educational information is divided into modules (complete and independent units, parts of information). A module is a block of information that includes a logically completed unit of educational material, a targeted program of action and methodological guidance that ensures the achievement of set goals. The concept of a module contains such a volume of educational material, thanks to which the primary acquisition of certain theoretical and practical skills for performing any specific work is ensured.